A ocorreência de erros formais na lavratura de autos de infração , nos períodos de 1997 a 1999 e de 2007 A 2009, na Secretaria da Fazenda do Ceará, e a influência da capacitação dos autuantes para os resultados obtidos - Ribeiro, Carlos Augusto Soares (2011)
The tax administration has as preponderant role to oversee the full tax compliance by taxpayers, leaving it to their agents when faced with situations characterized as illegal tax, effect the release of the tax due. The issuance of the tax assessment is an administrative act through which makes this release, and the same should, when it is developed, to meet all legal requirements, otherwise they will not fulfill its purpose. Therefore, this study was drawn up, intending to quantify and identify the main formal defects practiced when preparing the Tax Administrative Procedure within the Department of Finance of the State of Ceará. As hypotheses, these errors are the main reason why the litigation takes decisions against the State Treasury, and they occur mainly due to ignorance on the part of the active agent, the devices of the regulation of matter and the amount of hours training and trained servers directly influences the quality of violation reports issued. In this work we carried out a broad literature on the subject, and were used reports as the Administrative Litigation Tax. It was concluded by confirming the hypothesis that formal errors in the establishment of the Tax Administrative Process are the main reason why they are making by the litigation contrary to the State Treasury, not confirmed in this work, however, the hypothesis that number of hours of training and trained servers directly influences the quality of violation reports issued. It remains also confirmed that the formal errors committed in the preparation of PAT happen mainly due to ignorance on the part of the fiscal agent, the provisions governing the matter.